Strategi Menentukan Harga Pokok Produksi yang Kompetitif Menggunakan Metode Activity Based Costing di PT. XYZ Food - Bamban Handriyanto; Lukmandono Lukmandono (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2023)
PT XYZ Food realized the importance of accurate costing strategies to increase company profitability. The traditional method of determining the cost of goods manufactured led to undercosting or overcosting, which further resulted in a low selling price. Therefore, the company implemented the Activity Based Costing (ABC) method to calculate the cost of goods manufactured by identifying and classifying activities into four levels and setting cost targets for each activity level. The results of the ABC method showed that the cost of Snack Series 10 gr was Rp. 17,246 per kg and Mie Sedap Series 9 gr was Rp. 17,247 per kg. Through pricing structure simulations, the company could reach the Highest Retail Price of Rp. 500 without reducing margins, and even the margin of ABC was greater than the traditional method. Thus, the use of ABC in determining the cost of goods manufactured can help companies increase profits and get accurate prices in a competitive market.